IMPLEMENTING COMMUNICATIVE LANGUAGE TEACHING TO IMPROVE SPEAKING PERFORMANCE IN YOUNG ESL STUDENTS - Musoyeva Aziza Botirovna,; Orifjonova Ruxshona Baxtiyor qizi,; Shukurova Shaxodat Sharif qizi, (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: This theoretical paper examines the implementation of Communicative Language Teaching (CLT) as a pedagogical approach to enhance speaking performance among young English as a Second Language (ESL) learners. Through a comprehensive review of existing literature and theoretical frameworks, this study explores the principles of CLT, analyzes appropriate methodological approaches for young learners, and discusses the anticipated outcomes of implementing CLT in ESL speaking contexts. The analysis reveals that CLT, when adapted to the developmental needs of young learners through age-appropriate activities such as games, role-plays, and collaborative tasks, provides a robust framework for improving oral proficiency. The paper emphasizes the importance of meaningful communication, learner-centered instruction, and authentic language use in fostering speaking competence.